Protection of Intellectual Property Law (KI) Against the Results of Food and Beverage Entrepreneurship Products of NU 2 High School - Ifahda Pratama Hapsari; Vembri Aulia Rahmi; Iwan Sandi Pangarso (Kontribusia : Research Dissemination for Community Development, 2020)
The rapid development of industry triggers a reality that each region must have independence. Therefore, efforts to improve welfare continue to be made. One of the activities that can be carried out by entrepreneurship and producing a product is that later the product can be resold and can be imaged to get its legal protection. School support can also support the realization of a business that will run later. But the reality on the ground as experienced by high school 2 NU, Gresik Subdistrict with processed products in the form of food and soft drinks which are managed by the Adik-Adik who are in School, There are weaknesses and imperfections and implementation In the field of entrepreneurship they are engaged in, that is, there is no protection or understanding that the processed products are managed they can be registered and obtain a form of protection and patented. Motivation and skill, tenacity will be strong enough to build on human resources if their processed products in KI to achieve a sense of security and comfort and to realize a form of protection for entrepreneurs. adapt their processed products. Community service activities that involve a team of lecturers and students using the lecture method and discussion can improve the ability of business managers. The overall service activities can be said to be quite good with indicators of the success of mastery of the material on the concept of entrepreneurship and digital marketing.